The Implementation of MDGs Program on Eradication of Extreme Poverty and Hunger in Indonesia (2009-2014) - Syifa Zia Rahmah; Grace Lestariana Wonoadi; Achmad Zulfikar (Parahyangan Center for International Studies, 2019)
The study of the implementation of Millenium Development Goals (MDGs) program in Indonesia aims to find out the background and significance of the program taken by the government under President Susilo Bambang Yudhoyono in 2009-2014 on the issue of eradication of extreme poverty and hunger. The problem of extreme poverty and hunger in Indonesia has not been solved comprehensively. Therefore, the government had to provide the right program to end poverty. The research based on the qualitative method, which uses official reports, literature review and news articles as the sources. The result showed that the programs of eradication extreme poverty and hunger in 2009-2014 had been revised became three clusters. The first cluster aims to help and protects the social family guarantee and to assure the basic needs. The second cluster is the eradication of poverty and hunger through the social assistance program. The third cluster was focusing on eradication of poverty and hunger in term of economic matter. The government used the indicators by UNDP, as the base of the decision-making process, but also used the real condition of poor people in Indonesia as the main consideration.